Riemerella anatipestifer Type IX Secretion System Is Required for Virulence and Gelatinase Secretion - Guo, Yunqing; Hu, Di; Guo, Jie; Wang, Tao; Xiao, Yuncai; Wang, Xiliang; Li, Shaowen; Liu, Mei; Li, Zili; Bi, Dingren; Zhou, Zutao (Frontiers in Microbiology, 2017)
Riemerella anatipestifer (RA), a major causative agent of septicemia anserum exsudativa in domesticated ducklings, has a protein secretion system known as the type IX secretion system (T9SS). It is unknown whether the T9SS contributes to the virulence of RA through secretion of factors associated with pathogenesis. To answer this question, we constructed an RA mutant deficient in sprT, which encodes a core protein of the T9SS. Deletion of sprT yielded cells that failed to digest gelatin, an effect that was rescued via complementation by a plasmid encoding wild-type sprT. Complement-mediated killing was significantly increased in the deletion mutant, suggesting that proteins secreted by the T9SS are necessary for complement evasion in RA. Liquid chromatography-tandem mass spectrometry analysis revealed that RAYM_01812 and RAYM_04099 proteins containing a subtilisin-like serine protease domain and exhibiting extracellular gelatinase activity were secreted by the T9SS. Animal experiments demonstrated that the virulence of mutant strain ΔsprT strain was attenuated by 42,000-fold relative to wild-type RA-YM. Immunization with the ΔsprT protected ducks from challenge with RA-YM, suggesting that the former can be used as a live attenuated vaccine. These results indicate that the T9SS is functional in RA and contributes to its virulence by exporting key proteins. In addition, subtilisin-like serine proteases which are important virulence factors that interact with complement proteins may enable RA to evade immune surveillance in the avian innate immune system.